DSS (Decision Support System) Penilaian Kinerja Mahasiswa dengan Profile Matching - Didik Warasto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2017)
This research aims to design a teaching materials for increasing motivation and learning achievement of the students in Microcontroller course, Department of Electronics Engineering, Politama Surakarta. It also aims to identify effects of using Arduino Kit teaching materials in motivation and learning achievement. Data is taken from 2 groups of Assembly Language course, each has 32 students. Research instruments use questionnaire, pretest and post-test. The questionnaire uses 5-point Likert Scale. The pretest and post-test use objective test with 4 options. Data is collected and analyzed with SPSS v23. Homogeneity and normality test are used before testing hypothesizes. Hypothesizes are tested with nonparametric statistics Mann-Whitney U-Test. Research results show that the use of Arduino Kit instructional media has positive impact on both motivation and learning achievement. The average score of motivation of the treatment group (72,90) is higher than the average score of motivation of the control group (68,19). Results also show that the post-test average learning achievement of the treatment group (26,49) is higher than the average learning achievement of the control group 22,03.